If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11 = x + -1(-14) Multiply -1 * -14 11 = x + 14 Reorder the terms: 11 = 14 + x Solving 11 = 14 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 11 + -1x = 14 + x + -1x Combine like terms: x + -1x = 0 11 + -1x = 14 + 0 11 + -1x = 14 Add '-11' to each side of the equation. 11 + -11 + -1x = 14 + -11 Combine like terms: 11 + -11 = 0 0 + -1x = 14 + -11 -1x = 14 + -11 Combine like terms: 14 + -11 = 3 -1x = 3 Divide each side by '-1'. x = -3 Simplifying x = -3
| 3(f-4)=-9 | | Log(2x-40)=2 | | 5/x-2=7/x+4 | | 5/8x=9 | | 15k-1100=12k+200 | | x^2+4x-12=10x+4 | | 4logX=20 | | 54x^2-10x-1=0 | | 6(t+3)=6 | | 6(10x+16)=18 | | 1.3a+1.5=5.4 | | 21-2k=k/10 | | 3x-15=14-2x-6 | | 12(x-2)+7(y+1)=25 | | y=55x+200 | | (-3u+3)x(u^3-1)= | | y=17(4)-28 | | 2(2x+4)=3x+1 | | -4z+24=-3z-6 | | 12x+5=3x+19 | | x+2x+27+x=163 | | -(x-4)=-1 | | -10(x+4)=9 | | -11=17x-28 | | 5(8x+8)-2(2-7x)=12+55x | | 48y-63=37y+55 | | x-1.5y=-3 | | 16=10+3m | | 8y+1=-31 | | 4x^2+18x= | | 7(2+x)=3x+1 | | -6(k-2)-(-7k+1)=3 |